Communicative Types of Self-Disclosure in Public Speaking Setting - Kyrychuk, Larysa (East European Journal of Psycholinguistics, 2017)
The present paper focuses on the study of the communicative nature of self-disclosure as a technique of verbal influence on people. The phenomenon of self-disclosure is interpreted as the process of divulging private information to others. The aim of the study is to determine the specific features of self-disclosure in a public speaking context. The paper discusses the communicative conventions and parameters of the public speaking scenario as the factors that determine a certain manner of self-disclosing. The key assumption of the study is that public self-disclosure should be viewed as a tactic of self-presentation that promotes the speaker’s image building. In order to indicate the verbal forms that speakers use while disclosing private information in public the discourse and lexical-grammatical analyses of eight celebrity interview texts are conducted. The results of the research demonstrate that the speakers use recurrently certain verbal patterns which are identified as statements of self-description (it includes statements of self-confirmation, self-assurance, personal preferences and personal aspirations), self-narrative and attitude statements. The study also shows which types of the statements are used more frequently than the others, particularly, the statements of self-confirmation, personal aspirations and self-narratives are apparently preferred by the speakers as tactics of public self-disclosure. The paper highlights the fact that the self-disclosure tactics are employed by public speakers selectively and that their choice is motivated by the speakers’ strategic goal of impression management.ReferencesAltman, I., Taylor, D. A. (1973). Social Penetration: The Development of InterpersonalRelationship. New York, NY: Holl, Rinehart & Winston.Baumeister, R. F. (1982). A self-presentational view of social phenomena. PsychologicalBulletin, 91, 3–26.Carver, C. S., Scheier, M. R. (1998). On the Self-Regulation of Behavior. CambridgeUniversity Press.Cozby, P.C. (1973). Self-disclosure: A literature review. Psychological Bulletin, 79(2),73–91.Derlega, V. J., Metts, S., Petronio, S., Margulis, S. T. (1993). Self-Disclosure. NewburyPart, CA: Sage.Hargie, O. (2011). Skilled Interpersonal Interaction: Research, Theory and Practice.London: Reutledge.Johnson, J.A. (1981). The ‘self-disclosure’ and ‘self-presentation’ views of item responsedynamics and personality scale validity. Journal of Personality and Social Psychology,40(4), 761–769.Jourard, S. (1971). The Transparent Self. (2nd ed.).New York: Van Nostrand Reinhold.Leary, M. R. (1995). Self-Presentation: Impression Management and InterpersonalBehavior. Madison, WI: Brown & Benchmark.Leary, M. R. (1996). Self-Presentation: Iimpression Management and InterpersonalBehavior. Boulder, CO: Westview Press.Leary, M. R. (2012). Introduction to Behavioral Research Methods. (6nd ed.). Boston:Pearson.Leary, M. R., Kowalski, R. M. (1990). Impression management: A literature review andtwo-component model. Psychological Bulletin, 107(1), 34–47.Luft, J., Ingham, H. (1969). Of Human Interaction. Palo Alto, CA: National Press Books.Rosenfeld, L. B. (2014). Overview of the ways privacy, secrecy, and disclosure arebalanced in today’s society. In: Balancing the Secrets of Private Disclosure, (pp. 3 – 18).S. Petronio, (ed.). New York and London: Psychology Press.Schlenker, B. R. (1980). Impression management: the self-concept, social identity, andinterpersonal relations. Monterey, CA: Brooks/Cole.Schlenker, B. R. (1985). Identity and self-identification. In: The self and social life, (pp.65–99). B.R.Schlenker, (ed.). New York: McGrow-Hill.Schlenker, B. R. (2003). Self-presentation. In: Handbook of Self and Identity, (pp. 492–518). M. R.Leary, J. P.Tangney, (eds.). New York: Guilford.SourcesJ.K. Rolling meets Lauren Laverne, 2015.Oprah talks to Barack Obama, 2004. O, The Oprah magazine.Oprah talks to Daniel Pink, 2008. O, The Oprah Magazine.Oprah talks to Ellen De Generes, 2009. O, The Oprah Magazine.Oprah talks to Jay-Z, 2009. O, The Oprah Magazine.Oprah talks to Tine Fey, 2009, O, The Oprah Magazine.Oprah talks to Thich Nhat Hanh, 2010.8.The ultimate O interview: Oprah answers all your questions, 2010. O, the Oprah magazine.
Keywords: self-disclosure; self-presentation; public speaking; communicative tactic; private information; verbal pattern.